Relation between some climatic factors and the chemical composition of Tithonia diversifolia - Herrera, R.; Verdecia, D. M.; Ramírez, J. L.; García, M.; Cruz, Ana M. (Cuban Journal of Agricultural Science, 2017)
During two years the relation between some climatic factors and the chemical composition of Tithonia diversifolia was studied, using a completely randomized design and five replications, in brown soil with carbonate. The chemical composition indicators consisted of: NDF, ADF, lignin, cellulose, hemicellulose, cell content, organic matter, ashes, N, Si, P, Ca and Mg; while the climatic factors were the maximum, minimum and average temperatures, rain and number of rainy days. The results are expressed by the Pearson correlation coefficient in each seasonal period. In the rainy season, high and positive correlation coefficients were found between total rain and NDF, ADF, lignin and organic matter (0.87-0.97) and were negative for cellulose, cell content, ashes and N (between -0.88 and -0.97). The relation with the temperatures were variable and the highest value (r = 0.92) was recorded between the P and the average temperature. For the number of rainy days, there was a similar performance to that described above, but the coefficients were higher. In the dry season, there was a positive correlation between total rain and NDF, ADF, lignin, hemicellulose, ashes, P and Ca (0.52-0.88) and were negative with cellulose, cell content, organic matter and N (between - 0.55 and -0.88). For the number of rainy days there was similar performance, but the coefficients were higher and there was relation with the Si (r = -0.45). The linear multiple equations were established between the chemical composition indicators and some climatic factors, with high values of the determination coefficient, low standard error and high significance. The chemical composition indicators showed a specific response to climatic factors in each seasonal period, but the higher effect, expressed by the correlation coefficient, is related to the amount and distribution of precipitation. It is recommended to determine the mathematical model that allows to predict the performance of each indicator of the chemical composition with the climatic factors, as well as to perform this study in other plants of economic importance for animal feeding and to extend it to the secondary metabolites or antinutritional factors. Key words: temperature, rain, nitrogen, fiber